2020
DOI: 10.1186/s40563-020-00126-3
|View full text |Cite
|
Sign up to set email alerts
|

Bonding strength of benuang and duabanga glulams using their barks as phenol formaldehyde-filler

Abstract: In line with environmental issues and forest sustainability, tree bark of two species from tropical rain forests i.e. benuang (Octomeles sumatrana/BN) and duabanga (Duabanga moluccana/DB) was used as filler for phenol formaldehyde resin (PF-filler). The main objective of the research was to analyze effect of tree barks as PF-filler on bonding strength of BN and DB glulams produced. Four glue mixture compositions with ratio PF, technical filler, and tree bark filler, respectively are 10: 0: 0 (A); 10: 1.5: 0.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The partial replacement of wheat flour with chestnut and fir bark powders also resulted in the decrease of free formaldehyde content and the increase in plywood's mechanical properties [22]. Furthermore, Marbun et al [23] studied the effect of benuang (Octomeles sumatrana BN) and duabanga (Duabanga moluccana DB) barks as the filler for phenol-formaldehyde resin (PF) in glulam production. On the basis of the presented results, it was concluded that the bark of both species can be effectively used as a modifier of PF adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…The partial replacement of wheat flour with chestnut and fir bark powders also resulted in the decrease of free formaldehyde content and the increase in plywood's mechanical properties [22]. Furthermore, Marbun et al [23] studied the effect of benuang (Octomeles sumatrana BN) and duabanga (Duabanga moluccana DB) barks as the filler for phenol-formaldehyde resin (PF) in glulam production. On the basis of the presented results, it was concluded that the bark of both species can be effectively used as a modifier of PF adhesive.…”
Section: Introductionmentioning
confidence: 99%
“…Jahanshaei et al [ 14 ] developed an eco-friendly tannin-phenol formaldehyde resin to decrease the formaldehyde level of wood composites [ 15 ] using a bark alkaline extractive from lodgepole pine ( Pinus contorta ) to produce bio-based melamine formaldehyde resins. Benuang bark ( Octomeles sumatrana /BN) and duabanga bark ( Duabanga moluccana /DB) can act as filler in phenol-formaldehyde [ 16 ] adhesives. Red cedar bark ( Thuja plicata ) was analyzed in compounds with isocyanates (pMDI) resins [ 17 , 18 ]; the authors analyzed the influence of beech bark ( Fagus sylvatica ) in adhesive mixtures used in plywood (Ply) and [ 19 ] carried out research on the effects of using birch bark ( Betula pendula ) particles with various dimensions as a filler for urea-formaldehyde resin in Ply, similar to the study of [ 20 ], who analyzed the role of walnut, chestnut, fir, and spruce bark flours instead of wheat flour in Ply production.…”
Section: Introductionmentioning
confidence: 99%